Wavelet packet neural networks for texture classification - Sengur, Abdulkadir; Turkoglu, Ibrahim; Ince, M. Cevdet (Pergamon-Elsevier Science Ltd, 2007)
Texture can be defined as a local statistical pattern of texture primitives in observer's domain of interest. Texture classification aims to assign texture labels to unknown textures, according to training samples and classification rules. This paper describes the usage of wavelet packet neural networks (WPNN) for texture classification problem. The proposed schema composed of a wavelet packet feature extractor and a multi-layer perceptron classifier. Entropy and energy features are integrated wavelet feature extractor. The performed experimental studies show the effectiveness of the WPNN structure. The overall success rate is about 95%. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: wavelet decomposition; wavelet packet neural networks; texture classification; feature extraction